Meta-analysis: pioglitazone improves liver histology and fibrosis in patients with non-alcoholic steatohepatitis - Boettcher, E. (2011)
SUMMARY: BACKGROUND: Thiazolidinediones (TZDs) have been used in the treatment of non-alcoholic steatohepatitis (NASH). However, the magnitude of treatment response associated with TZDs in improving liver histology in NASH has not been quantified systematically. AIM: To conduct a meta-analysis of randomised, placebo-controlled clinical trials (RPCTs) using pioglitazone and rosiglitazone in the treatment of NASH. METHODS: Pubmed/MEDLINE and Cochrane Central Register of Controlled Trials 2010 were searched until September 2010 and four RPCTs were identified. Peto odds ratios (ORs) and their respective 95% confidence intervals (CIs) were used to assess the efficacy of TZDs in improving liver histological parameters. RESULTS: Four good quality RPCTs derived from three continents were included. The meta-analysis showed that TZDs (n = 169) were significantly better than placebo (n = 165) in improving ballooning degeneration, lobular inflammation and steatosis with combined ORs of 2.11 (95% CI, 1.33–3.36), 2.58 (95% CI, 1.68–3.97) and 3.39 (95% CI, 2.19–5.25) respectively. The improvement in combined necroinflammation with TZD (n = 58) vs. placebo (n = 52) was also statistically significant (combined OR 6.52[95% CI, 3.03–14.06]), but improvement in fibrosis was not. When pioglitazone (n = 137) was analysed alone, the improvement in fibrosis with pioglitazone (n = 137) vs. placebo (n = 134) (combined OR 1.68 [95% CI, 1.02–2.77]) was statistically significant. The total body fat slightly decreased in the control, while it markedly and highly significantly increased with TZD treatment. CONCLUSIONS: Thiazolidinediones significantly improve ballooning degeneration, lobular inflammation, steatosis and combined necroinflammation in patients with NASH. Pioglitazone may improve fibrosis. Larger randomised, placebo-controlled clinical trials are needed to examine the efficacy of thiazolidinediones in improving NASH fibrosis.